2011
DOI: 10.1002/bmc.1696
|View full text |Cite
|
Sign up to set email alerts
|

Determination of therapeutic oligonucleotides using capillary gel electrophoresis

Abstract: Oligonucleotides have developed into highly versatile and selective therapeutics over the past 20 years. More than five discrete mechanisms of action have been reported and more than 10 different chemical modifications have been used to extend their in vivo half-life and reduce their toxicity. Capillary gel electrophoresis (CGE) has been used extensively for the quantitative analysis of oligonucleotide therapeutics in both preclinical and clinical studies since the 1990s. The success of CGE is based on its ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 55 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…Efficient separation and quantitation of the ( n − 1)‐mers from full‐length synthetic oligonucleotides can be achieved using capillary gel electrophoresis rather than with HPLC (Gilar et al, ; Srivatsa et al, ). Capillary electrophoresis has excellent performance characteristics when used as a QC method both for the assessment of synthetic oligonucleotide purity and for the determination of shortmers in plasma, tissues and urine (Chen & Bartlett, ; Leeds, Graham, Truong, & Cummins, ; Palm & Marko‐Varga, ). Yet it should be noted that using capillary gel electrophoresis in a quantitative fashion is challenging because small changes in the ionic strength of the samples will alter the amounts loaded on the column (Chen & Bartlett, ).…”
Section: Different Types Of Oligonucleotide Impurities and Degradatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient separation and quantitation of the ( n − 1)‐mers from full‐length synthetic oligonucleotides can be achieved using capillary gel electrophoresis rather than with HPLC (Gilar et al, ; Srivatsa et al, ). Capillary electrophoresis has excellent performance characteristics when used as a QC method both for the assessment of synthetic oligonucleotide purity and for the determination of shortmers in plasma, tissues and urine (Chen & Bartlett, ; Leeds, Graham, Truong, & Cummins, ; Palm & Marko‐Varga, ). Yet it should be noted that using capillary gel electrophoresis in a quantitative fashion is challenging because small changes in the ionic strength of the samples will alter the amounts loaded on the column (Chen & Bartlett, ).…”
Section: Different Types Of Oligonucleotide Impurities and Degradatiomentioning
confidence: 99%
“…Capillary electrophoresis has excellent performance characteristics when used as a QC method both for the assessment of synthetic oligonucleotide purity and for the determination of shortmers in plasma, tissues and urine (Chen & Bartlett, ; Leeds, Graham, Truong, & Cummins, ; Palm & Marko‐Varga, ). Yet it should be noted that using capillary gel electrophoresis in a quantitative fashion is challenging because small changes in the ionic strength of the samples will alter the amounts loaded on the column (Chen & Bartlett, ). Comparisons between capillary electrophoresis and other techniques such as RP‐HPLC, ion‐exchange HPLC, mass spectrometry and PAGE demonstrated that the highest resolution and precision were obtained when using capillary electrophoresis (Ball & Packman, ; Chen & Bartlett, ; Cohen, Vilenchik, Dudley, Gemborys, & Bourque, ; Gelfi, Perego, Morelli, Nicolin, & Righetti, ; Metelev & Agrawal, ; Srivatsa et al, ).…”
Section: Different Types Of Oligonucleotide Impurities and Degradatiomentioning
confidence: 99%
“…A four-color readout obtained during DNA sequencing is depicted in Figure 20. Determination of therapeutic oligonucleotides, including antisense DNAs, aptamers, ribozymes, DNAzymes, siRNAs, and miRNAs, by CGE is of great interest as well [173]. Forensic applications include analysis of short tandem repeats (STRs) loci in DNA for determination of human identity, mitochondrial DNA analysis, single nucleotide polymorphisms, mutation detection, and nonhuman DNA analysis [172].…”
Section: Ce Of Peptides and Proteinsmentioning
confidence: 99%
“…These effects are not permanent, meaning that if the siRNA administration is interrupted, the gene silencing is aborted accordingly. [1,[13][14][15][16][17] Most of these methods use ion-pairing agents in order to enhance the chromatographic properties of the target analytes. By targeting performance influencing genes with siRNA in athletes, the legal requirements of a gene doping rule violation are fulfilled and open a new dimension in doping controls.…”
Section: Introductionmentioning
confidence: 99%